Manufacturing FDI in India versus China: A Malaysian Perspective - Avalani, Haetal (2008)
Foreign Direct Investment (FDI) is viewed as a major stimulus to economic growth in developing countries and there has been intense competition among the countries to attract FDI. In recent years a new trend has emerged where developing and transition economies have become important sources of outward FDI. Malaysia a developing country with diverse natural resources and a relatively large manufacturing base has been following this trend. This paper examines the determinants of manufacturing FDI in China and India. The focus of this study is the determinants from a Malaysian perspective. India and China have emerged as the fastest growing economies in the world in the last decade. The large economy coupled with its large population base makes both the countries important destinations for both market seeking and efficiency seeking FDI. However, China which reformed its economy earlier is much ahead than India and this makes it the obvious decision among investors especially in the manufacturing industry. This study involves input and feedback from the industry where existing Malaysian investors are interviewed to gauge the investor sentiment in both countries and provide an understanding of what matters for Malaysian investors. The FDI determinants in both India and China are evaluated to provide a guide for potential investors from the manufacturing industry in Malaysia. Although China is the front runner, India has some great potential both in market growth and labour supply dimensions provided the government follows its economic reform agenda.